The Social System of Creativity: How Publishers and Editors Influence Writers and their Work. - Paton, Elizabeth (International Journal of the Book, 2012)
The creation of a book does not end with a draft manuscript. Rather, writers seek out publication and communication with an audience as the culmination of their work. In general terms, this process involves a publishing house accepting the draft manuscript, structural and surface editing, printing and criticism and then the eventual sale and reading of the book by an audience member. At each stage, individual actors and institutions other than the writer make decisions that can affect the content, style, design and reception of the work as well as the publication of future works and the writer's career. As such, publication and communication represent a network of relationships an individual writer must negotiate before they may be considered creative. This complies with Csikszentmihalyi's systems model, which posits that, in order to understand creativity in any area, it is necessary to investigate not only the individual and the domain of knowledge they draw on but also how this social system operates, making judgements on and shaping that knowledge. Accordingly, this paper investigates writers' points of engagement with the social system of fiction writing, specifically their interactions with publishers and editors, and how these networks of judgement and support influence both the writer and their work.